Understanding "˜citizenship' to protect human rights of liquefaction survivors in South Palu - Swantoro, Aris (Jurnal Civics: Media Kajian Kewarganegaraan, 2024)
Disaster management is a critical component of national development, particularly in the aftermath of natural disasters. The relocation process of liquefaction disaster survivors in Petobo, located in South Palu, Central Sulawesi, underscores the pivotal role of the government in safeguarding Indonesian citizens' rights, including providing adequate housing within a healthy and secure environment. This research was conducted in the wake of the disaster with the primary objective of evaluating the legal protection and human rights afforded to survivors residing in Petobo Village, which has been designated as a red zone due to the severity of the disaster. The study uncovered significant damage to infrastructure, loss of life, and ecosystem degradation as direct consequences of the disaster. These findings underscore the government's obligation to provide permanent housing (hence HUNTAP) to fulfill the basic needs of survivors. Providing decent housing is fundamental to ensuring the well-being and dignity of every citizen affected by the disaster. Moreover, it aligns with the core principles of citizenship and human rights, which are essential for fostering sustainable and harmonious communities, particularly in regions grappling with the aftermath of natural calamities. Shortly, the relocation of liquefaction disaster survivors in Petobo, South Palu, Central Sulawesi, highlights the government's pivotal role in safeguarding its citizens' rights, especially in times of crisis. By prioritizing permanent housing and ensuring a healthy and secure environment for survivors, the government demonstrates its commitment to upholding human rights and fostering resilient communities in disaster-affected areas.